Multigeneration Inheritance through Fertile XX Carriers of an NR0B1 (DAX1) Locus Duplication in a Kindred of Females with Isolated XY Gonadal Dysgenesis - Michela Barbaro; Jackie Cook; Kristina Lagerstedt-Robinson; Anna Wedell (International Journal of Endocrinology)
A 160 kb minimal common region in Xp21 has been determined as the cause of XY gonadal dysgenesis, if duplicated. The region contains the MAGEB genes and the NR0B1 gene; this is the candidate for gonadal dysgenesis if overexpressed. Most patients present gonadal dysgenesis within a more complex phenotype. However, few independent cases have recently been described presenting with isolated XY gonadal dysgenesis caused by relatively small NR0B1 locus duplications. We have identified another NR0B1 duplication in two sisters with isolated XY gonadal dysgenesis with an X-linked inheritance pattern. We performed X-inactivation studies in three fertile female carriers of three different small NR0B1 locus duplications identified by our group. The carrier mothers did not show obvious skewing of X-chromosome inactivation, suggesting that NR0B1 overexpression does not impair ovarian function. We furthermore emphasize the importance to investigate the NR0B1 locus also in patients with isolated XY gonadal dysgenesis.